2018
DOI: 10.1002/ffo2.7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of graphical format on judgmental forecasting accuracy: Lines versus points

Abstract: People made forecasts from real data series. The points in the series were un‐trended and independent. Hence, forecasts should have been on the mean value. However, consistent with previous research on forecasting biases, forecasts were too close to the last data point. It appears that forecasters see positive sequential dependence where none exists. In three experiments, we examined this bias in different types of forecasting task: point forecasting, probability density forecasting, and interval forecasting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Harvey and Bolger (1996) found that trends for instance were more easily discernible when the data was displayed graphically rather than tabular. Additionally, simple variations in presentation such as line graphs versus point graphs can alter accuracy (Theocharis et al, 2018).…”
Section: Supporting Judgment In Practice 141mentioning
confidence: 99%

Forecasting: theory and practice

Petropoulos,
Apiletti,
Assimakopoulos
et al. 2020
Preprint
Self Cite
“…Harvey and Bolger (1996) found that trends for instance were more easily discernible when the data was displayed graphically rather than tabular. Additionally, simple variations in presentation such as line graphs versus point graphs can alter accuracy (Theocharis et al, 2018).…”
Section: Supporting Judgment In Practice 141mentioning
confidence: 99%

Forecasting: theory and practice

Petropoulos,
Apiletti,
Assimakopoulos
et al. 2020
Preprint
Self Cite
“…During model development, expert elicitation, a formal process of extracting expert knowledge while mitigating bias (Hemming et al, 2018), can be employed to inform model structure (e.g., Bertone et al, 2016). End users should also be consulted regarding forecast dissemination methods to ensure correct interpretation of forecast output and maximize forecast utility (Berthet et al, 2016;Gerst et al, 2020;Theocharis & Smith, 2019). For example, interviews and focus groups with end users of NOAA's Climate Prediction Center climate outlook visualizations guided updates of NOAA's air temperature and precipitation color maps for improved forecast interpretability (Gerst et al, 2020).…”
Section: Integration Of End Users Into the Forecast Processmentioning
confidence: 99%
“…Therefore, graphs based on the characteristics inherent to them, the graph will be appropriate when the data presented has a trend and is used to forecast future conditions, for this type of data the graph can better show a general picture and the relationship between the data presented. Conversely, the use of tables is beneficial if used on data that requires an emphasis on data values at a particular point in time and will be more useful to facilitate the explanation of data that have specific benefits [12], [17] and [18].…”
Section: Graphic and Decision Makers Productivitymentioning
confidence: 99%
“…Researchers in psychology find that humans tend to minimize cognitive efforts to achieve the accuracy of the decisions they make [17]. Several other studies have also found that managers take a lot of advantage from decision aids to reduce the effort needed to do a job ( [22] and [11].…”
Section: Information Modalities and Decision Qualitymentioning
confidence: 99%